Character Education Values Used in the Avengers: Endgame Movie - Anggun Purnomo Arbi (JournEEL, 2021)
Abstract This research was aimed to describe the character education values used in the Avengers: End Game Movie. Movie is described as the series of moving pictures combined with sound effects. Character education values .This study applied library research as it described the results of study. The data of this study were the phenomena and facts classified into the character education values. The source of data were the facts or phenomena shown in the movie scenes and the movie transcription of Avengers: Endgame. This study used two instruments called: the researcher himself and the documentation. The object of this study was a movie entitled “Avengers: Endgame”. In collecting the data of this research, the researcher used documentary technique including watching the movie, reading the movie’s screenplay and taking a note. The researcher used the theory of content analysis (Ary, 2010) to analyze the data. Based on the results of the study, the researcher found nine types of character education values covering responsible, love and affection, honesty, hardworking, tolerant, curious, patriotic, creative, and communicative.